Leave no one behind: including the health of prisoners in international development frameworks is essential for achieving sustainable development goals - Wanapa Naravage; Marc van der Putten; Anja Krumeich; Luca Falqui; Rodger Doran (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The pledge of the 2030 Agenda for Sustainable Development is "to leave no one behind." However, there are significant groups of people who are at risk of being left behind. The health and social issues facing prisoners are well known, but past initiatives to address them through international development initiatives have failed to gain widespread support. The purpose of this paper is to advocate for inclusion of prison health care in current international development frameworks such as Universal Health Coverage and the 2030 Sustainable Development Goals. Design/methodology/approach - This is a commentary paper. Findings - The governments of most countries have accepted both the 2030 Agenda for Sustainable Development and Universal Health Coverage as frameworks for future national development planning. Including prison health care in these frameworks will provide a powerful platform for those advocating for better prison health services and will allow governments wary of offending public opinion to make significant changes to the way prisons are managed. Providing better prison health care services will not only lead to better long-term population health outcomes overall but will also contribute to achieving the 2030 Agenda aspiration to "leave no-one behind." Originality/value - This paper provides a discussion of current international development guidance and identifies that prison health care is not sufficiently recognized as an essential contributor to achieving the sustainable development goals.